Corporate governance and firm performance within the Russian agri-food sector: does ownership structure matter? - Alisher Tleubayev; Ihtiyor Bobojonov; Taras Gagalyuk; Emma García Meca; Thomas Glauben (International Food and Agribusiness Management Review, 2021)
This article provides pioneering empirical evidence on the ownership structure and firm performance relationship for the case of corporate agri-food companies in Russia. While Russia plays a vital role in the global agri-food system, its domestic agri-food production is evidently dominated by a small number of corporate enterprises, which are in turn characterized by high ownership concentration. We employ unique panel data obtained from 203 companies for the years between 2012 and 2017. A random effects model was used to analyze the impacts of ownership concentration and ownership identity on the firms' financial performance, measured by return on assets and return on sales. Our results indicate an inverse U-shaped association between ownership concentration and firm performance, with average level of ownership concentration found to be on the descending range of the inverse U-shaped curve. Moreover, we observe a similar quadratic relationship between ownership concentration by government and directors and firm performance. On average, ownership by directors was found to be on the ascending range and below the peak point, suggesting a potential for further performance improvement, while the impact of agroholding ownership was found to be linear and positive.
Keywords: M14; Q12; Q13; 650; corporate governance; ownership structure; agri-food enterprises; firm performance; Russia